The Difficult Politics of Peace: Rivalry in Modern South Asia, Christopher Clary - Ms. Maryyum Masood (CISS Insight Journal, 2022)
India and Pakistan have been involved in a long-standing rivalry over the erstwhile princely state of Jammu and Kashmir (J&K) for seven decades. Since their independence in 1947, both states have fought three wars and border skirmishes frequently occur at the Line of Control (LOC), the line that divides the part of J&K each state controls. The unresolved issue of J&K has been a bone of contention between the two neighbors besides other issues like the Rann of Kutch, Siachein etc. In order to ensure control over these areas, both countries allocate a large portion of their budget on defence even while facing other economic challenges, the author argues. The book under review is authored by Christopher Clary, an Assistant Professor of Political Science at the University at Albany, State University of New York, and a Nonresident Fellow with the South Asia Program of the Stimson Center in Washington, DC. The book is divided into eight chapters and provides a chronology of major events and developments that mark the rivalry between the two neighboring states. Clary attempts to dissect the cycle of peace-building and war-making between the rival states by taking into account various developments such as; 1948 war, 1965 war, Tashkent Declarataion 1966, 1971 war, Kargil conflict, the then-Indian Prime Minister Atal Bihari Vajpayee’s visit to Lahore in 1999, and Musharraf’s four stage Kashmir plan etc.